Analisa Tingkat Pengetahuan Ibu Dengan Kunjungan Balita ke Posyandu Kabupaten Demak: Analysis of Mother's Knowledge Level with Toddler Visits to Posyandu, Demak Regency - Titik Kurniawati; Widyah Setiyowati; Dwiki Endah Widiastuti (YCMM, 2022)
The Toddler Mortality Rate (AKABA) in Central Java Province in 2015 was 11.64/1,000 KH. Meanwhile, in 2016 there was an increase of 11.8/1,000 KH. And in 2017 it decreased to 10.47/1,000 KH. More than 1,500 posyandu in Demak Regency are active in carrying out various activities for community empowerment in the health sector. Based on posyandu data at Bumi Batursari Mas Housing, Mranggen District, Demak Regency in January-August there were 25 toddlers, and every month mothers of toddlers come to the posyandu at the Bumi Batursari Mas Posyandu, there is one toddler whose development is not in accordance with his age and there are 2 cases of stunting. This study was to analyze the relationship between mother's knowledge and frequency of posyandu visits at Poyandu Bumi Batursari, Mranggen District, Demak Regency. Posyandu is a community-based health effort, known to the public in both urban and rural areas. This type of research is correlative with a cross sectional approach. The population was 25 mothers, with a saturated sample (25 mothers were all taken), and the sampling technique was total sampling. The results showed that the knowledge of mothers under five about posyandu was mostly good, namely 21 (84%) respondents, with a good frequency of visits, namely 22 (88%) respondents and there was a relationship between mother's knowledge and frequency of visits to posyandu, with a p value of 0.002. Suggestions for the community to actively participate in posyandu activities and health workers to further improve health education about posyandu.